2014
DOI: 10.3390/s140917832
|View full text |Cite
|
Sign up to set email alerts
|

Data Fusion to Develop a Driver Drowsiness Detection System with Robustness to Signal Loss

Abstract: This study proposes a drowsiness detection approach based on the combination of several different detection methods, with robustness to the input signal loss. Hence, if one of the methods fails for any reason, the whole system continues to work properly. To choose correct combination of the available methods and to utilize the benefits of methods of different categories, an image processing-based technique as well as a method based on driver-vehicle interaction is used. In order to avoid driving distraction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Other applications of the proposed system include teleoperation of vehicles and driver behavior investigations such as works done in Friedrichs and Yang (2010) and Samiee, Azadi, Kazemi, Nahvi, and Eichberger (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other applications of the proposed system include teleoperation of vehicles and driver behavior investigations such as works done in Friedrichs and Yang (2010) and Samiee, Azadi, Kazemi, Nahvi, and Eichberger (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have assessed, classified and predicted drowsiness states ( Ji et al, 2004 , 2006 ; Sayed et al, 2012 ; Singh and Banga, 2013 ; Kusuma and Sunitha, 2014 ; Samiee et al, 2014 ). However, no definite or effective methods emerged from this research for determining when a warning signal should be presented to the driver.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to predict the psychological rating on drowsiness using behavioral and physiological measures [24,28,29]. However, currently it is impossible to predict the point in time with high crash risk (crash in simulated driving) before such a crash occurs.…”
Section: Prediction Of Point In Time With High Crash Risk By Integratmentioning
confidence: 99%
“…Sayed and Eskandarian [23] succeeded in achieving an accuracy of about 90% in classifying drivers as being sleep deprived or non-sleep deprived using driver steering data. Samiee et al [24] evaluated the arousal level classified as being alert or drowsy using vehicle dynamic data such as vehicle longitudinal position and duration of eye closures, and showed that the proposed method could differentiate between the alert and the drowsy states with an accuracy of more than 87.78%. Eskandarian et al [25] and McDonald et al [26] indicated the effectiveness of such vehicle-based measures for assessing drowsiness.…”
Section: Prediction Of Point In Time With High Crash Risk By Integratmentioning
confidence: 99%
See 1 more Smart Citation